Tutankhamun in Portugal: reports in te portuguese press (1922-1939) - Sales, José das Candeias (2020)
The research project Tutankhamon em Portugal. Relatos na imprensa portuguesa (1922-1939) aims to understand how the discovery of Tutankhamun's tomb on the 4th of November of 1923 was reported by the Portuguese periodicals at a time when its international counterparts, especially the British and the French, published almost daily news about it. We quickly realized that, although Portugal was not at the time a country with Egyptological experience and tradition, and that it crossed one of the most troubled political and social periods in its history, the Portuguese newspapers and magazines not only did not ignore the subject, but on the contrary, they gave it a place of prominence in its pages, mainly during the years of 1923 and 1924. Thus, we propose to demonstrate how sources not commonly used in the studies of the Reception of Antiquity – newspapers and magazines – can also effectively contribute to realize how the civilization of ancient Egypt was received, in the 1920s of the 20th century, in Portugal. The great archaeological discovery of Carnarvon and Carter was a powerful motto that allowed the periodicals of the time to bring closer the Egyptian civilization to its readers. In Portugal, the richness of its history, the artistic wealth, and the mysterious and superstitious religion associated with this civilization, were widely reported and thus actively contributed to the readers' view of the ancient Egyptian people, their history and culture.